Is a Plasmodium lactate dehydrogenase (pLDH) enzyme-linked immunosorbent (ELISA)-based assay a valid tool for detecting risky malaria blood donatioFls in' Africa? - ATCHADE, PASCAL; Doderer-Lang, Cecile; CHABI, Nicodeme; Perrotey, Sylvie; Abdelrahman, Tamer; Akpovi, D. Casimir; ANANI, LUDOVIC YAOVI; BIGOT, KOFFI ANDRÉ; SANNI, AMBALIOU; Candolfi, Ermmano (My University, 2013)
Background: Malaria IS a leading cause of mortality in southern Benin. The main causative agent, Plasmodium falCiparum, poses a threat on critical transfusions in pregnant women and children. This study's objective was to compare the performance of different malaria screening methods in blood donors in southern Benin, a malaria-endemic country. Methods: Blood from 2.5 15 voluntary blood donors in Benin was collected over a period of 10 months in ethylenediaminetetraacetic acid (EDTA) tubes, which were then c1assified according to extraction time: long rainy season, short dry season, short rainy season, and long dry season. Microscopie examination was used to count parasites. Parasite density (PD) was expressed as the number of parasites per I-IL of blood. Pan Plasmodium pLDH detection was assessed by an ELISA-malaria antigen test. Using crude soluble P. falciparum antigens, an ELISA-malaria antibody test detected anti-Plasmodium antibodies. Results: Among the 2,515 blood donors (2,025 males and 488 females) screened, the rate of asymptomatic Plasmodium carnage was 295/2,515 (11.72%,95% CI: 10.5-13.1 %). Males had a higher infection rate (12.4%) than did females (8.8%). Parasite density was very low: between seven and 100 parasites per I-IL of blood was reported in 80% of donors with parasitaemia. Three Plasmodium species were diagnosed: P. falciparum in 280/295 patients (95.0%), Plasmodium malariae ln 14/295 (5.0%), and Plasmodium ovale in 1/295 (0.34%). Malaria prevalence in donors was higher during the lainy seasons (13.7%) compared with the dry seasons (9.9%). The use of a highly sensitive assay enabled pan Plasmodium pLDH detection in 966/2,515 (38.4%, 95% CI: 36.5%-40.3%). Malaria antibody prevalence was 1,859/2,515 (73.90/0,95% CI: 72.16-75.6%). Donors' antigenaemia and antibùdy levels varied significantly (P <0.05) over the course of the four seasons. The highest antigenaemia rate 323/630 (51.3%), was observed during the short rainy season, while the highest antibody prevalence, 751/886 (84.7%), was recorded during the long dry season. Conclusion: Blood donations Infected with Plasmodium can transmit malaria to donation recipients. Malaria diagnostic methods are currently available, but the feasibility criteria for mass screening in endemic areas become preponderant. Detection of the pLDH antigen seems to be an adequate screening tool in endemic areas, for this antigen indicates parasite presence. Routine screening of ail donated blood wou Id prevent infected blood donations and reduce P falciparum transmission in critical patients, such as children and pregnant women. This tool wouId also decrease rnedical prophylaxis in donation recipients and contribute to lower Plasmodium resistance.
Keywords: Malaria; Transfusion; Plasmodium falciparum; pLDH; Antibodies